British Virgin Islands : Financial Sector Assessment Program Update Documentation; Technical Note on Corporate and Trust Services Providers. (IMF Staff Country Reports; Country Report ;, 2010)
This study reviews the structure of the Trust and Corporate Service Providers (TCSP) sector in the British Virgin Islands (BVI), focusing on their role in the offshore financial sector, and seeks to assess the legislative framework in place as well as effectiveness of implementation and enforcement of this framework. Structure of the TCSP industry and the key features of legislative framework are also discussed. The global financial crisis has also resulted in a significant decline in asset values. The Financial Services Commission Act (FSCA) provides a strong framework for the supervision of other financial services in the jurisdiction.